A bottom-up optimization model for the long-term energy planning of the Greek power supply sector integrating mainland and insular electric systems - Georgiou, Paraskevas N. (Computers & operations research, 2016)
The energy planning of power sector constitutes a multifaceted challenge for policy makers, incorporating a variety of economic, technological, environmental, political and social aspects in order to ensure the unhindered equilibrium between electricity demand and electricity supply. This paper presents a deterministic bottom-up Mixed Integer Linear Programming model for the long-term energy planning of national power supply systems, having special focus and modeling effort on the peculiar case of Greece. It is a least cost optimization based model being expanded and enhanced with the integration of electric interconnections and the evident participation of environmental dimension. Its superstructure consists of multiple mathematical expressions representing power demand patterns, technical constraints, operation rules, penetration potential of energy sources, economic aspects, technological availability, environmental obligations and other sectoral targets and commitments applying in the electricity supply field. Its main contribution lies on the holistic methodological approach adopted, concerning the discrete electric systems of mainland and insular areas in Greece by proposing a novel way of simulating the potentiality of their submarine interconnection. The present model is applied on a real case study concerning the Greek electricity planning problem for the period 2014–2024, through the elaboration of two alternative evolution scenarios. The underlying objective is multifarious: (a) to deliver the portfolio of new capacity investments, the fuel mix trend, the penetration of renewable energy sources and the progress of achieving country׳s commitments and targets, and (b) to investigate and highlight the potential economic, energy and environmental benefits arising from the electrical interconnection of Greek islands to the main continental power system.